Detecting Occupations in German Texts : Challenges and Data - Reiser, Thomas [Verfasser]; Dörpinghaus, Jens [Verfasser]; Steiner, Petra [Verfasser] (My University, 2025)
"This paper is concerned with the detection and classification of occupational titles in German texts, with a focus on the linguistic and structural challenges that are unique to the German language. The study utilizes an extensive dataset on job title variants to assess rule-based and language model-based methodologies across diverse corpora, encompassing historical documents and parliamentary proceedings. The findings indicate that rule-based methods demonstrate robust performance, particularly in structured texts, while large language models exhibit complementary strengths in recognizing complex terms. The work makes a significant contribution to the field by providing valuable annotated data and methodological insights." (Authors' abstract, BIBB-Doku)
Keywords: T 3 Forschungsmethoden; 370; 300; Texterkennung; Berufsklassifikation; Large Language Model